2016
DOI: 10.15359/ree.20-2.21
|View full text |Cite
|
Sign up to set email alerts
|

La acción tutorial académica en pequeños grupos: Una experiencia educativa con estudiantes universitarios

Abstract: This study establishes three objectives. The first, describe the main characteristics of a tutorial action program developed within an academic subject in a Faculty of teacher training. The second, determine the level of appraisement of the degree of importance given by students to a group of transversal skills and the kowledge level related to the research methodology during the tutorial action. The third, discuss the role of the tutorial action at the university in the new European Higher Education Area. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Recently, Martínez-Bello and Martínez-Rojas (2016) have described the main characteristics of a tutorial action program developed within an academic subject in a Faculty of teacher education. The authors found that a tutorial action was an positive alternative experience in order to facilitate communication and participatory processes with university students.…”
Section: Experiences Regarding Tutorial Action With University Studentsmentioning
confidence: 99%
“…Recently, Martínez-Bello and Martínez-Rojas (2016) have described the main characteristics of a tutorial action program developed within an academic subject in a Faculty of teacher education. The authors found that a tutorial action was an positive alternative experience in order to facilitate communication and participatory processes with university students.…”
Section: Experiences Regarding Tutorial Action With University Studentsmentioning
confidence: 99%